Characterizing Utilization and Outcomes of Digoxin Immune Fab for Digoxin Toxicity - Sophia Sheikh; Taylor Munson; Gerard Garvan; Claire Layton; Dawn Sollee; Colleen Cowdery; Alexa Peterson; Lindsay Schaack Rothstein; Morgan Henson; Hayley Gartner; Michael Ujhelyi (Adis, Springer Healthcare, 2024)
Abstract Background Digoxin is a widely prescribed drug for congestive heart failure and atrial fibrillation. Digoxin has a narrow therapeutic index and toxicity can develop quite easily. Digoxin immune fab (DIF) is an effective treatment for toxicity, however there are limited studies characterizing its impact on clinical outcomes in real-world clinical practice. Objectives The aim of this study was to identify factors and healthcare outcomes associated with digoxin immune fab (DIF) treatment in patients with confirmed/suspected digoxin toxicity. Methods An IRB-approved retrospective chart review of digoxin toxic patients (2011-2020) presenting at an academic healthcare system was conducted. Demographic and clinical data were collected. Patients were stratified by DIF treatment versus non-DIF treatment. DIF utilization patterns (appropriate, use when not indicated, or underutilized) were determined using pre-defined criteria. Severe digoxin toxicity was defined as having one or more of the following: mental status disturbances, antiarrhythmic therapy, acute renal impairment or dehydration, serum digoxin concentration (SDC) > 4 ng/mL, or serum K+ > 5 mEq/mL. Logistic multivariable regression analysis evaluated factors associated with DIF use. All statistical analyses were performed in R version 4.1. Results Data from 96 patients (non-DIF treated group = 49; DIF treated group = 47) were analyzed. DIF was used appropriately in 70 patients (73%), underutilized in 19 (20%), and administered to 7 (7%) patients when it was not indicated. Several clinical parameters differentiated the DIF from the non-DIF group (p < 0.05) including higher mean SDC (3.41 ± 1.63 vs 2.87 ± 1.17), higher mean potassium (5.33 ± 1.48 vs 4.55 ± 0.87), more toxicity severity (85% vs 49%), and more likely to require cardiac pacing (26% vs 4%). Digoxin toxicity resolved sooner in the DIF group (coefficient − 0.702, 95% CI − 1.137 to − 0.267) (p < 0.01) and they had shorter intensive care unit lengths of stay (12.4 ± 20.3 vs 24.4 ± 28.7 days; p = 0.018). The all-cause mortality rate in patients appropriately managed with DIF therapy versus those patients where DIF was underutilized was 11% and 21%, respectively. Conclusions Based on our study population, DIF therapy appears to be beneficial in limiting duration of toxicity and intensive care unit lengths of stay in digoxin toxic patients. Although DIF was appropriately utilized in most cases, there was a relatively high proportion of cases in which DIF treatment was either underutilized or not indicated.